Better Response and Prognosis of Venetoclax Plus Hypomethylating Agents Over Intensive Chemotherapy in Young Adults With Newly Diagnosed ASXL1‐Mutated Acute Myeloid Leukemia - Yiming Cai; Jingwen Rui; Zhengwen Ding; Judan Xie; Zhou Jin; Jinyan Xiao; Yang Xu (Cancer Medicine)
ABSTRACT Background ASXL1 is one of the most frequently mutated genes in acute myeloid leukemia (AML) and retains adverse‐risk status in intensively treated cohorts according to 2022 European Leukemia Net (ELN) risk criteria. The therapeutic and prognostic impacts of hypomethylating agents (HMAs) and venetoclax in young adults with ASXL1‐mutated AML is unclear. Methods Eighty‐one patients with ASXL1‐mutated AML ≤ 60 years old were retrospectively analyzed. The effects of HMAs plus venetoclax on treatment response and its prognostic value were compared with intensive chemotherapy (IC) and HMAs combined with low‐intensity chemotherapy. Results Intensive chemotherapy independently predicted a worse treatment response (IC vs. HMA + venetoclax, OR = 0.183, 95% CI 0.048–0.693, p = 0.012) and inferior overall survival (OS) (IC vs. HMA + venetoclax, HR = 3.316, 95% CI 1.332–8.255, p = 0.010). After 15 patients with favorable cytogenetics or mutations were excluded, the HMA + venetoclax combination still outweighed IC with respect to treatment response (IC vs. HMA + venetoclax, OR = 0.063, 95% CI 0.012–0.332, p = 0.001) and OS (IC vs. HMA + venetoclax, HR = 3.072, 95% CI 1.216–7.758 p = 0.018) in patients with an adverse risk according to 2022 European Leukemia Net guidelines. Allogeneic hematopoietic stem cell transplantation independently predicted superior OS (HR = 0.234, 95% CI 0.088–0.626, p = 0.004). Additionally, in patients receiving HMAs combined with venetoclax, the G646fs variant of the ASXL1 mutation was associated with a lower complete remission or with an incomplete hematological recovery rate (4/7 vs. 2/19, 42.9% vs. 10.5%, p = 0.026) and worse event‐free survival (median, 14.0 months vs. not reach, p = 0.045). Conclusion HMAs and venetoclax could benefit newly diagnosed younger patients with ASXL1‐mutated AML.